ASSESSING THE EFFECTIVENESS OF ISO 45001 STANDARD ON SUSTAINABLE INNOVATION MANAGEMENT IN A CERTIFIED ALGERIAN PORT COMPANY -CASE STUDY OF INTERNATIONAL DJEN DJEN PORT- - DJENOUHAT, Assia; REZAK, Rayane; TRIFA, Mohamed (The journal of contemporary issues in business and government, 2024)
The ISO 45001 relates to sustainable development goals. ISO 45001 management standard focuses on occupational health and safety. This study was conducted to examine the relationship between ISO45001 standards and sustainable innovation management about the implementation of the ISO 56000 standard in the port company DJEN DJEN, Jijel, Algeria. Data was collected using questionnaires from a random sample 26 responds. A quantitative methodology has been chosen and treated by SPSS.v26. The findings imply that the port is already certified of ISO 45001 standard in order to consistently balance the economics with the environment and enhance skills and staff’s involvement in the company.